Representation of Huyula Local Wisdom Values as Character Strengthening for Elementary School Students - Dali, Kasim; Rahmatiah, Rahmatiah; Yunus, Rasid (Journal of Basic Education Research, 2025)
Purpose of the study: This study aims to analyze the strengthening of student character through the value of Huyula local wisdom that emphasizes the spirit of gotong royong at elementary school 21 Telaga Biru, Gorontalo. Methodology: The method used was qualitative case study with data collection techniques through interviews, observation, and document analysis, involving teachers, principals, parents, and traditional leaders. Main Findings: The results showed that huyula values are applied in thematic learning, extracurricular activities, and student social interactions, and form attitudes of empathy, tolerance, and responsibility. However, implementation is still constrained by low teacher understanding, exclusivity of student friendships, and minimal participation. Teacher training and strengthening learning methods that encourage active participation and inclusive interactions are needed. Novelty/Originality of this study: The novelty of this study is that it reveals how Huyula's local wisdom values are not only taught as theory, but actually applied in daily life in elementary schools. This research shows that if local cultural values are incorporated into students' learning and activities, then character education can be built more strongly and relevant to the environment where children grow up